2017
DOI: 10.1589/rika.32.473
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Functional Residual Capacity Increase on Trunk Rotation of Healthy Adults

Abstract: 竹内 誠貴 1,2) 工藤 卓人 3) 藤田 拓 4) 石川 良太 5) 宇井 秀斗 6) 遠藤 沙紀 7) 小山 千賀穂 8) 佐藤 榛花 9) 鈴木 里沙子 10) 森岡 奏子 11) 渡辺 麻美 12) 久保 晃 13) 石坂 正大 13)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The change in FFD also depended on the amount of inhaled air. An expansion of the thorax with an increase in the FRC led to decreased mobility of trunk rotation as per our previous study2, 4 ) . In this study, we could demonstrate decreased active trunk flexion with a quantitative increase in FRC, in addition to trunk rotation.…”
Section: Discussionsupporting
confidence: 80%
“…The change in FFD also depended on the amount of inhaled air. An expansion of the thorax with an increase in the FRC led to decreased mobility of trunk rotation as per our previous study2, 4 ) . In this study, we could demonstrate decreased active trunk flexion with a quantitative increase in FRC, in addition to trunk rotation.…”
Section: Discussionsupporting
confidence: 80%
“…This study involved a descriptive laboratory design, which has been described in previous articles 7 , 8 , 9 ) . Kim et al suggested that thoraco-lumbo-pelvic rotation in supine position as leg lateral reach test and showed good reliability.…”
Section: Methodsmentioning
confidence: 99%
“…To measure AROTAR, the participant was in a supine position with both glenohumeral joints fully flexed 8 ) . In this position, one examiner stood at the cranial end and fixed both sides of scapula of the participant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation